Universal Secondary Education (USE) in Guyana - World Bank (Washington, DC, 2013)
In 2002, Guyana adopted a broadly-based five year plan (2003-2007) to achieve universal secondary education (USE), with a strategy to convert secondary classes in primary schools and grade 7-10 community high schools into General Secondary Schools (GSS) in which all students could present for the Caribbean Examination Certificate (CXC) or an alternative competency-based Certificate. Current status of secondary education (chapter one) summarizes the performance of public schools in Guyana against the Ministry of Education (MOE) policy on universal secondary education (2002), trends evident in the annual statistical digests, and the broad issues presented to Senior MOE officers on 13 December and to the Minister on 19 December 2007. Improving secondary student participation (chapter two) examines national and regional trends in population, enrollment, low levels of apparent transition from primary to secondary schools, poor secondary school entry examination (SSEE) results and issues related to the "size" of secondary schools. Upgrading and qualifying teachers (chapter three) identifies small school enrollment issues in earlier chapters with the enrollment required to offer a viable secondary curriculum, improve teacher qualification/training and reduce attrition rates. Student learning outcomes (chapter four) links poor student attendance, poor primary (SSEE) examination outcomes, limited secondary curriculum offerings, low rates of survival from grade 7 to grade 11 to the reported CXC results for Guyana. Schools and infrastructure (chapter five) presents the assessment that low student "demand" and a shortage of qualified teachers prevents Guyana achieving USE. Increasing the "supply" of secondary school places would not achieve USE unless other investments are made to improve the pool of suitably qualified students. Secondary education resources and budgets (chapter six) reviews education expenditure as aproportion of budget and the salary/non-salary recurrent expenditure for primary ("Tops") and secondary schools.